Future directions for HIV service delivery research: Research gaps identified through WHO guideline development. - Nathan Ford; Ingrid Eshun-Wilson; Wole Ameyan; Morkor Newman; Lara Vojnov; Meg Doherty; Elvin Geng (PLoS Medicine)
Nathan Ford and co-authors discuss the systematic identification of research gaps in improving HIV service delivery.